COMPOSITION OF RESULTS OF HILL AND MORNING GARDEN NETWORK CAPACITY IN ALAI SUB-DISTRICT, WEST TEBING SUB-DISTRICT, REGENCY OF MERANTI RIAU PROVINCE - Alhamidi Alhamidi; Arthur Brown; Isnaniah Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractFisheries is one of the activities directly related to the management and utilization of biological resources from shipping. This research was conducted for 6 days in Alai Village, Tebing Tinggi Barat Barat District, Meranti Islands Regency, Riau Province. This study aims to determine the composition of the results of research involving morning and evening drift gills. The composition of the catch of the drift gill fishing gear operated in the Malacca Strait by the fishermen of Alai Village provided 4 types of fish taken. Among them are the Lomek fish (Horpoden neherus), the prickly fish (Ilisha elongata), the happy fish (Eleutheronema tetradactylum) and the stingray (Batoidea). Individual catches in one experiment are a maximum of 578 tails and a minimum number of catches in a selection of 5 tails. When viewed from the fish weight data, fish that have a maximum weight in one fold 0.25 kg and a minimum of 0.07 kg. The total catch during the 12 shifts was 468 kg of Lomek fish, 235 kg of prickly fish, 2.1 kg of fermented fish and 10 kg of stingrays. Keywords: Fisheries, Composition, Morning and Evening, Alai Village, and Catches